Bioethical considerations about water fluoridation: a critical review. - María Elisa Quinteros (Universidad de Concepción., 2016)
Dental caries is one of the oral pathologies with greater burden of disease in the Chilean population. Fluoridation of drinking water has been used as a caries prevention strategy. However, its application as a public policy has been questioned since its implementation. The aim of this article is to analyze whether fluoridation of drinking water is a justified measure in reducing the incidence and prevalence of caries from the perspective of bioethics, taking into account the current evidence on its effectiveness. The arguments reviewed are based on the belief that water fluoridation is effective and, in general terms, ethically acceptable. A recent systematic review concludes that there is not enough evidence to support fluoridation as a public policy. There is a gap of knowledge that ought to be closed so that public health authorities can assess the significance of the intervention and make a democratic decision on its continuation or suspension based on scientific evidence. This decision should be informed and disseminated within the community.